Analisis Penggunaan Bentuk Sapaan di Pondok Pesantren Al-Muayyad Surakarta - Ana Sofiyatul Azizah (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2017)
This study aims to describe (1) the type of greeting, and (2) the factors that affect the use of the greeting form in Pondok Pesantren Putri Al Muayyad Surakarta. The subject of this study is the overall use of greetings in Pondok Pesantren Putri Al Muayyad Surakarta, while the object of this study are the types of greetings and factors that affect the use of the greeting form in Pondok Pesantren Putri Al Muayyad Surakarta. Data collection was done by observation and interview method, while data analysis was done by method of padan and method of agih. The type of method used is the reference method of reference subclass and pragmatic subtypes, while the technique used to analyze the data with the method is the permutation technique. The validity of the data is obtained by triangulation technique done by source. The results of this study are as follows. First, greetings are grouped by layers and layers of meaning. Based on layers of form, greetings can be grouped into three traits, i.e phonological features, morphological features, and syntactic characteristics. In layers of meaning there are greetings based on semantic features. Based on the phonological characteristics, the greeting can be distinguished into greetings with the addition of the final hamzah /? / Segment segment, the segment segmentation in the initial term, and the segment segmentation at the end of the term. Based on the morphological characteristics, greetings can be divided into four kinds, namely basic form greeting, bercy form greetings, re-form greetings, and compound greetings. Based on syntactic characteristics, greetings can be divided into two, namely grammatical units and syntactic distributions. Based on the grammatical unit, the greeting is shown in phrase form, while from the syntactic distribution, the greeting can be classified into three, namely the greeting in front of the clause, in the middle of the clause, and at the end of the clause. Based on semantic characteristics, greetings can be divided into six kinds, namely greeting the name of self, greeting pronouns persona / pronoun, greeting the word relatives, greeting position, hermitage title, and greeting intimate. Secondly, there are five factors that affect the use of greeting forms, namely age, gender, situation, social status, and relationship of intimacy.